Change Readiness During Ongoing Restructuring at the Agricultural Engineering and Modernization Agency - Annisa Hana Fitriani; Furqon Syarief Hidayatulloh; Yunus Triyonggo (Goodwood Publishing, 2026)
Purpose: This study analyzes the key individual and organizational factors influencing employee readiness for change during ongoing restructuring at Indonesia’s Badan Standardisasi Instrumen Pertanian Modernisasi dan Pertanian (BRMP) and proposes evidence-based recommendations to support leadership decision-making in managing the transition. Research Methodology: A mixed-method design was used. The quantitative phase used Structural Equation Modeling-Partial Least Squares (SEM-PLS) with data from 100 civil servants across 13 organizational units selected through purposive sampling based on direct restructuring experience. The sample size met the SEM-PLS adequacy criteria. The qualitative phase involved in-depth interviews with six management representatives of the company. Results: All five hypotheses were supported in this study. Previous restructuring experience had the strongest effect on readiness (β = 0.408, p < 0.001), followed by organizational valence (β = 0.246, p = 0.001), communication systems (β = 0.240, p = 0.004), and self-efficacy (β = 0.150, p = 0.039). The model explained 80.2% of the variance in readiness (R² = 0.802). The interviews highlighted that reciprocal communication, active top-management involvement, and fair recognition systems are key strategic levers for enhancing readiness. Conclusions: Change readiness in BRMP is shaped by accumulated restructuring experience, perceived organizational benefit, communication quality, and individual confidence. The findings demonstrate that prior restructuring experience, when actively managed through institutional communication, can build rather than erode readiness across multiple restructuring cycles. Limitations: The cross-sectional design and specialized sample of 100 respondents limit the temporal generalizability. Contributions: This study extends the organizational readiness framework to a repeated, compressed, and ongoing restructuring context in Indonesian public institutions. The integration of SEM-PLS with in-depth management interviews provides both structural and strategic perspectives on readiness factors.